2004
DOI: 10.1177/107602960401000413
|View full text |Cite
|
Sign up to set email alerts
|

Antiphospholipid Syndrome Associated with Malignant Mesothelioma Presenting with Superior Vena Cava Thrombosis: A Case Report

Abstract: A 59-year-old woman who had dyspnea and neck swelling for 10 days was admitted to the hospital. Malignant peritoneal mesothelioma was diagnosed previously. According to the clinical findings, and laboratory and pathologic examination, the patient was found to have disseminated venous thrombosis and antiphospholipid syndrome, which is treatment-resistant autoimmune paraneoplastic syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…In fact, only one case of SLE as a syndrome related to PM has been described since 1980 [5]. Instead, the association of PM or peritoneal mesothelioma with inflammatory myopathies, seronegative rheumatoid arthritis, and some atypical vasculitis has been described and reported as paraneoplastic syndromes, although scleroderma-like and SLE-like syndromes (especially subacute cutaneous SLE) have also been reported [7–12]. …”
Section: Discussionmentioning
confidence: 99%
“…In fact, only one case of SLE as a syndrome related to PM has been described since 1980 [5]. Instead, the association of PM or peritoneal mesothelioma with inflammatory myopathies, seronegative rheumatoid arthritis, and some atypical vasculitis has been described and reported as paraneoplastic syndromes, although scleroderma-like and SLE-like syndromes (especially subacute cutaneous SLE) have also been reported [7–12]. …”
Section: Discussionmentioning
confidence: 99%
“…This has also been noted in other series. [4,6,8,12,15] Cancer, either overt or occult, [2,30] is quite common in patients with UEDVT (more than 40% of cases). [1][2][3][4][5][6][7][8]9,12] Independent of catheter placement, malignancy is an independent risk factor for VTE.…”
Section: Discussionmentioning
confidence: 99%
“…[28,31] Upper extremity deep vein thrombosis is sometimes a harbinger of occult cancer. [30] Ten patients with occult cancer were admitted with signs suggestive of SVC syndrome and/or UEDVT, and the malignancy was detected later. This also occurred in the series by Girolami et al [30] Patients with indwelling CVCs constitute a particularly high-risk population, especially those suffering from cancer and undergoing chemotherapy or those subjected to invasive hemodynamic monitoring, chronic parenteral nutrition, hemodialysis, or transvenous pacing.…”
Section: Discussionmentioning
confidence: 99%
“…Thromboembolism may occur as part of a paraneoplastic syndrome or because of a decrease in anticoagulation factors. According to Ozkan et al, 3 mesothelioma cells and cell lines have been shown to secrete a pleiotropic cytokine, interleukin 6, which potentiates the production of platelets. However, the underlying mechanism of thrombosis in mesothelioma is still unknown.…”
Section: Discussionmentioning
confidence: 99%